AVALIAÇÃO DE MEMBRANAS DE OSMOSE INVERSA NO TRATAMENTO DE ÁGUAS DE PURGA DE TORRES DE REFRIGERAÇÃO DE INDÚSTRIA PETROLÍFERA COM FINALIDADE DE REUSO - Nascimento, Jailton Ferreira do (2007)
In the present study the possibility of treatment for reuse of the purge water from the Refinery Duque de Caxias cooling towers by reverse osmosis (RO) was evaluated. The oil industry consumes huge volumes of water in the industrial refining operations and, due to the increasing demands and changes in the environmental legislation, reinforcing the reuse of it, the purge waters present high flows and chemical composition characteristics that make them proper for treatment for reuse. The RO process has two fundamental advantages for desmineralized water production in the industry: to decrease (or even to eliminate) the demand for chemical reagents used in the water treatment; and to reduce the effluent volumes. The characteristics of two commercial RO membranes (RO-1 polyamide and RO-2 cellulose acetate) were studied using a methodology established for this purpose, and the rejections for different chemical species were evaluated in the purge water from cooling towers. In general, rejections of chemical species higher than 90% were obtained with two RO membranes, and the characteristics of the water treated with them were comparable to those obtained with the conventional treatments. There was an increase in the water pH after the treatment using RO, so a final adjustment of the water pH is recommended before its use. The polyamide membrane presented better acting for the treatment of the purge water studied and the results point out the potential of employment of the RO membranes in the treatment of the cooling towers purge water from Refinery Duque de Caxias (Petrobras/Reduc).